230 Referral patterns and uptake of risk reducing surgery for non-brca genes associated with increased risk of epithelial ovarian cancer. (18th September 2019) - Lee, S; Bhuptani, B; Turecamo, S; Gerber, D; Smith, J; Pothuri, B
Abstract : Objectives: To identify referral patterns and uptake of risk reducing surgery (RRS) in patients with non- BRCA genes associated with an increased risk of epithelial ovarian cancer. Methods: A chart review of patients with mutations in MLH1, MSH2, EPCAM, MSH6, PMS2, RAD51C/D, BRIP1 was conducted from 2015–2018. Patients with BRCA1/2 and variants of uncertain significance were excluded ; MSH6 and PMS2 were included (though recent change to insufficient evidence). Primary outcomes of interest were referral to a gynecologic oncologist and the uptake of RRS. Results: Of 78 patients, 18 had undergone surgical management for treatment of cancer prior to genetic testing and were excluded. The majority of the patients (41 of 60, 68%) with non- BRCA actionable mutations were associated with Lynch Syndrome (LS). Of these patients, 23 of 60 (56%) were seen by gynecologic oncologists. Twenty of 41 (49%) underwent RRS. Excluding the MSH6 and PMS2 patients, 9 of 21 (43%) of patients with LS underwent RRS. Among patients with the non- BRCA and non-LS associated genes ( RAD51C, RAD51D, BRIP1 ) the most common reason for testing was family history of cancer (10 of 19). Fifteen of 19 were referred to a gynecologic oncologist; all patients with BRIP1 mutation were referred, while 70% of those with RAD51/D were referred. Among this subset of patients, 9/19 (47%) patients underwent RRS; the remaining patients were screened with surveillance ultrasounds and/or CA-125. Conclusions: Two-thirds of patients with non- BRCA genes associated with increased risk of ovarian cancer were referred to gynecologic oncologists, with a 48% of uptake or RRS.